The efficiency of the economic septic tank in the treatment of domestic wastewater and black water in rural areas (Research, Society and Development, 2021)
Wastewater treatment in rural areas is important to prevent the pollution of aquatic environments and to protect the health of the population. Centralized treatment systems present a high cost, making the use of decentralized systems attractive. The use of septic tanks for on-site treatment of residential (single-family) is an attractive alternative within the context of Brazilian sanitation. Thus, the main objective of this study was to analyze the efficiency of the Economic Septic Tank in the treatment of wastewater of two residences located in a rural area. Two systems were installed: the first treat sanitary wastewater of a residence with three residents (A) and the second treat only the water from the toilet of a residence with five residents (B) (Black Water). For both systems, A and B, removal efficiencies were obtained in relation to total suspended solid (75%), biochemical oxygen demand (58 and 55%), and chemical oxygen demand (61 and 60%), respectively. Removal efficiencies were close, indicating that the system works satisfactorily in both systems, considering values indicated in the literature.